DETERMINING THE LAW GOVERNING THE NATURE OF A CASE IN INTERNATIONAL ARBITRATION (Singaporean Journal of Business Economics and Management, 2016)
Foreign investment plays a key role in economic development. Indeed, it is this type of investment that provides the necessary economic factors, namely investment and technical knowledge, for economic growth. Advent of new means of global communication and advances made in a wide range of science fields has led to enormous and more complicated international transactions. The resulting disputes and complication are obviously beyond the scope of local courts which deal with local lawsuits. In fact, many international commercial disputes referred to local courts led to lengthy and expensive court hearings and has caused a number of problems for the parties involved. Furthermore, international arbitration was established and was later improved to an extent that in most international business contracts, both parties agree that should any dispute arise in connection with their contract, they will resolve it through international commercial arbitration. Therefore, determining the law governing international commercial arbitration is of paramount importance. This paper aims to analyze various theories on determining the law that governs arbitral vote.